Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

Nanette - Gadsby, Hannah (2018)
L'humoriste australienne Hannah Gadsby redéfinit l'humour standard en combinant lignes assassines et révélations troublantes sur les genres, la sexualité et l'enfance.
Keywords: approches et analyses; australie; cours; discours dominant; fem3500; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; océanie; premier cycle; queer; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques

Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences